(untitled) (The Pakistan Development Review, 1970)
In this paper, a set of coefficients is derived which can be used to project West Pakistan’s private consumption in the medium and longer term. For ten urban and rural income groups separately, income, price and cross elasticities of demand have been calculated. Thus, the methodology permits to trace the influence of changes in incomes, income distribution and prices on consumption. 1.2 Most development models concern themselves with aggregate income effects only, and assume constant income distribution and prices. This may be warranted as long as no structural shifts occur. Insofar as development implies structural shifts, there may be an inconsistency. Apart from this, the attainment of a more equitable income distribution is more and more being emphasized as an independent goal of socio-economic planning. Changes in distribution are more often than not at least partly the result of changes in relative prices. Obviously, then, both incomes and prices must be included in the planning framework if anything is to be said about the effect of planned development on equity.